Extracellular vesicles containing ACE2 efficiently prevent infection by SARS‐CoV‐2 Spike protein‐containing virus. Issue 2 (28th December 2020) - Cocozza, Federico; Névo, Nathalie; Piovesana, Ester; Lahaye, Xavier; Buchrieser, Julian; Schwartz, Olivier; Manel, Nicolas; Tkach, Mercedes; Théry, Clotilde; Martin‐Jaular, Lorena
Abstract: SARS‐CoV‐2 entry is mediated by binding of the spike protein (S) to the surface receptor ACE2 and subsequent priming by host TMPRSS2 allowing membrane fusion. Here, we produced extracellular vesicles (EVs) exposing ACE2 and demonstrate that ACE2‐EVs are efficient decoys for SARS‐CoV‐2 S protein‐containing lentivirus. Reduction of infectivity positively correlates with the level of ACE2, is much more efficient than with soluble ACE2 and further enhanced by the inclusion of TMPRSS2.